The “Pocket book of primary health care for children and adolescents”: WHO standards for improving paediatric and adolescent primary care in Europe, Central Asia and worldwide - Krüger, Carsten; Huss, Gottfried; Yasmin, Farzana; Weigel, Ralf (Frontiers in Pediatrics, 2024)
Paediatric primary care is more frequently provided both by physicians other than specialised paediatricians as well as non-physician cadres in Europe and globally.• The quality of paediatric primary care including a focus on preventive measures is rather variable and often does not comply with agreed international standards. • WHO Europe developed standards for paediatric primary care applicable to the WHO Europe region and globally to improve the provision and outcome of paediatric primary care across all settings. • These standards were published in an open-access pocketbook and in an open-access app, both accessible free-of-charge. • Although originally intended for use in the WHO Europe region, the pocketbook provides valuable information for all settings of paediatric primary care worldwide.